Multi-Level Post-Training Evaluation Framework for Management Development Programs at PT Garuda Maintenance Facility Aero Asia Tbk - Muhammad Rafly Zinedine Zhilaal; Majang Palupi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Leadership development programs in safety-critical industries require robust evaluation mechanisms to demonstrate organizational value, yet most organizations confine assessment to Level 1 satisfaction surveys. This study investigates post-training evaluation practices for management development programs at PT Garuda Maintenance Facility (GMF) Aero Asia Tbk, Indonesia's premier aviation Maintenance, Repair, and Overhaul (MRO) provider, and develops a comprehensive evaluation framework grounded in the Kirkpatrick-Phillips model. Employing a qualitative descriptive-analytical approach within a design and development research paradigm, the study analyzed 638 module-level evaluation responses and 584 qualitative participant comments across three programs: the Operational Leadership Program (OLP), MRO Management, and MRO Finance. Thematic analysis, content analysis of training syllabi, and descriptive quantitative analysis were integrated through methodological triangulation. Findings reveal that GMF's evaluation is uniformly confined to Level 1 reaction measurement, producing consistently high satisfaction scores while Levels 2 through 5 remain entirely absent, a pattern termed the evaluation ceiling paradox. The study proposes an integrated ADDIE-Kirkpatrick-Phillips framework encompassing enhanced reaction surveys, pre-test and post-test instruments, 360-degree behavioral assessments, results tracking templates, and ROI calculation guidelines, differentiated by program type and contextualized for the MRO industry and Indonesian BUMN governance setting. The framework is designed for phased 24-month implementation leveraging existing technology infrastructure.